تجلّيات الشّعر الحرّ في الأدب العربيّ: (Manifestations of Free Verse in Arabic Literature) - Bin Saleh عبد الحليم; Moussa Camara محمّد (At-Tajdid - Intellectual Refereed Journal, 2019)
This study does not seek to issue judgements of right or wrong on new forms of Arabic poetry that contradicted the classics. It seeks to examine the historical development of free verse through its various stages and changes. The study uses inductive, descriptive and analytical approaches to conclude that Arabic free verse has evolved in two main stages; the first is the stage of indicators and the second is the stage of growth. The first stage took place in 1946-1921 and the second stage that included publicity and laying down the foundations and rules started in 1947 till today. There is not a distinguished third stage, and there is not a standout pioneer in the first stage that can champion that period as there were many free verse poems in various newspaper in 1921 in particular. The pioneer of the second stage is Ali Ahmad Bakathir, as detailed in the study. Keywords: Free verse, Arabic literature, Renewal, Indicators and development.